Small-diameter optical fibre sensor embedment for ambient temperature cure monitoring and residual strain evaluation of CFRP composite laminates produced by vacuum assisted resin infusion - Rocha, Helena Cristina Lopes (2021)
Out of autoclave (OoA) processing techniques, such as liquid composite moulding techniques (LCM) and, particularly, the vacuum assisted resin infusion (VARI) technique, are being used, with increasing success, in replacement of prepreg/autoclave technologies to produce structural aircraft/aerospace polymer composite parts, due to its better cost effectiveness and competitiveness. This work aims to embed Fibre Bragg grating (FBG) sensors to monitor the VARI manufacturing of carbon fibre reinforced polymer (CFRP) composites and evaluate the associated phenomena: ambient curing and post curing reactions and resulting residual strains. The curing kinetics of the epoxy resin system alone was initially studied through isothermal differential scanning calorimetry (DSC) tests and applying the isoconversional Friedman method, and further studied by strain monitoring during ambient curing and post curing resorting to FBG sensors. The FBG sensors in the CFRP laminates were able to detect a subtle increase of strain as infusion of the CFRP started and to measure decreasing strain as resin filled in the dry fabric layers. Subtle strain decrease revealed forming crosslink bonds. Compressive strains measured by the FBG sensors during post curing show that further crosslink takes place. A comparison of resultant residual strains was made between specimens with embedded FBG sensors on small-diameter optical fibres (SDOF) and on large-diameter optical fibres (LDOF).